Bimbingan Kelompok Teknik Permainan Board Game Emotional Quest Terhadap Peningkatan Regulasi Emosi Siswa - Muhammad Iqbal Fanani; Dewi Lianasari; Astiwi Kurniati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Emotion regulation is an essential ability that students need to recognize, manage, and appropriately express their emotions in daily life. Low understanding of emotion regulation may lead to aggressive behavior, poor self-control, and difficulties in social interaction and learning processes. Therefore, effective group guidance services that align with adolescent developmental characteristics are needed. This study aims to examine the effect of group guidance using theÂ Emotional QuestÂ board game technique on improving students’ understanding of emotion regulation among eighth-grade students of the Special Program 2 atÂ MTs Negeri 1 Magelang.Â This study employed a quantitative approach with a pre-experimental design using a one group pretest–posttest design. The research subjects were selected through purposive sampling, consisting of six students who demonstrated low levels of emotion regulation understanding based on the pretest results. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using the paired sample t-test with the assistance of SPSS version 25.Â The results showed a significance value of 0.001 (p < 0.05), indicating a significant difference between pretest and posttest scores of students’ emotion regulation understanding. Descriptively, there was a 16.68% increase after the implementation of group guidance using the Emotional Quest board game technique. These findings indicate that the intervention has a significant effect on improving students’ understanding of emotion regulation. This study provides practical implications for school counseling services in designing innovative, interactive interventions that meet students’ emotional developmental needs.